DETERMINAN PENCIPTAAN LAPANGAN KERJA DI INDONESIA - Falah, Halimy Widya; Syafri (Media Ekonomi, 2024)
This research aimed to investigate the determinants of job creation in Indonesia. The research uses panel data with a time period of 2012 until 2022 and the area coverage is 33 Provinces in Indonesia. The analysis technique used in this study is panel data regression with the selected model being the Fixed Effect Model. Independent variables included changes in technology, consumption, investment, wages, labor productivity, and minimum wages. Job creation was measured using data on the number of employed people from Central Bureau of Statistics. The research findings indicate that job creation is significantly influenced by consumption and investment. Interestingly, labor productivity exhibits a negative relationship, contrary to the positive impact of technological change. This finding contrasts with the prevailing theory that posits a positive relationship between the two. Furthermore, the minimum wage policy does not demonstrate a significant impact on job creation, despite the fact that wages themselves have a significant negative impact.